Paradigm Shift in Qur’anic Studies: From Textual Orthodoxy to Contextual Hermeneutics in Indonesian Islamic Universities (2018-2024) - Danial; Masyhuri Rifai; Muhammad Shaleh Assingkily (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This study examines the paradigm shift in tafsir research at State Islamic Universities (PTKIN) across Sulawesi, addressing a significant research gap in understanding regional patterns of epistemological transformation in Qur'anic studies. While previous studies have explored tafsir research trends at individual institutions, none have systematically mapped multi-institutional shifts using scientific paradigm theory. Employing Kuhn's paradigm shift theory as an analytical framework, this qualitative study analyzes 713 student theses from four institutions (UIN Alauddin Makassar, IAIN Kendari, UIN Datokarama Palu, and STAIN Majene) during 2018-2024, supplemented by in-depth interviews and field observations. The findings reveal a significant transformation from textual-normative approaches (tahlili, maudhu'i) to contextual-sociological methodologies (living Qur'an, hermeneutics, ma'na-cum-maghza), accelerated by the COVID-19 pandemic, supervisor orientations, and curriculum policies. This shift reflects an epistemological reorientation from understanding the Qur'an as static text to dynamic discourse continuously produced through context-text dialogue. The study contributes theoretically by applying Kuhn's framework to Islamic studies and practically by providing strategic recommendations for adaptive curriculum reform and locality-based research development in Qur'anic studies.